Perubahan kadar hemoglobin akibat terapi kurkuminoid ekstrak rimpang kunyit dibandingkan natrium diklofenak pada penderita osteoartritis - Nyoman Kertia; Ahmad Husain Asdie; Wasilah Rochmah; Marsetyawan Marsetyawan (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2011)
Background: In general, patients with osteoarthritis require long live treatments, especially anti-infammatory drugs. Non steroidal anti infammatory drugs are mostly follow by some side effects such as dyspepsia and gastrointestinal bleeding. The use of natural medicine for rheumatic diseases have commonly been practiced worldwide.Objectives: To learn the changes of hemoglobin level due to treatment with curcuminoid from Curcuma domestica Val. rhizome extract compared to diclofenac sodium as anti-infammatory agent for the treatment of osteoarthritis.Methods: This research is a prospective randomized open end blinded evaluations (PROBE). Patients treated with 30 mg curcuminoid from Curcuma domestica Val. rhizome extract or 25 mg diclofenac sodium three times daily for 4 weeks respectively.The hemoglobin level was checked before and after treatment. Results: A total of 80 patients with knee osteoarthritis participated in this study. There was no signifcant difference in the frequency of sex, educational level, duration of suffering, percentage of co-morbidities in both groups. There was no signifcant different of hemoglobin level before treatment between both treatment group. The hemoglobin level was increase signifcantly in curcuminoid treatment groups while no signifcant change in diclofenac group. Treatment with curcuminoid increasing the hemoglobin level signifcantly compare to diclofenac sodium (p=0.03).Conclusion: Treatment with curcuminoid from Curcuma domestica Val. rhizome increasing the hemoglobin level signifcantly compare to diclofenac sodium treatment for osteoarthritis.